(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
Since the development of Western culture, mathematics has been used in other areas of scientific work. Biological Mathematics as a discipline integrates the tools and potential of mathematics in the life sciences, giving an epistemic basis to its theoretical bases. This essay makes a brief state of the art on the epistemological association that unites them and even makes them indissoluble, allowing both to generate the necessary methods to explain the processes of life, the mechanisms of inheritance and the way in which this evolves. Mathematical modelling, differential equations, and computer use are presented as benefits that mathematics provides disciplinary support to the life sciences.